Tensile and bending behaviors and characteristics of laminated Ti-(TiBw/Ti) composites with different interface status. (1st January 2017) - Liu, B.X.; Huang, L.J.; Kaveendran, B.; Geng, L.; Cui, X.P.; Wei, S.L.; Yin, F.X.
Abstract: A series of laminated Ti-(TiBw/Ti) composites fabricated at different diffusion welding temperatures of 1100 °C, 1200 °C and 1300 °C were subjected to tensile and bending tests. The results showed that the interfacial bonding strength, interfacial toughness and residual stress gradually increased with the increasing fabrication temperature. Therefore, along the transversal direction, the laminated composites fabricated at 1300 °C revealed the highest tensile strength and fracture elongation. However, the highest tensile strength (694 MPa) and elongation (22.7%) along the longitudinal direction, was recorded with the laminated composites fabricated at 1200 °C due to reasonable interfacial bonding and residual stress. Interestingly, the laminated composites fabricated at 1100 °C exhibited the highest bending fracture toughness and fracture work along arrester orientation. Due to the weak interfaces, the crack propagation path was displaced by delamination cracks and re-nucleated multiple tunnel cracks, which in turn lead to reduction in stress intensity of the main crack. This was beneficial to the toughening of the laminated Ti-(TiBw/Ti) composites.